Recent works carried out at the IDIEM by the group in charge of probabilistic strength of materials - P. Kittl; G. Díaz (Materiales de Construccion, 1990)
This updating review describes, from the conceptual standpoint, all the research works so far carried out at the IDIEM by the group in charge of Probabilistic Strength of Materials as well as research activities under way at present. This description considers three aspects. First, the general purposes of the commented discipline and the discussion of its theoretical foundations are presented. In the second place, an analysis is conducted in connection with materials subjected to diverse stresses of tension, compression, shearing, bending, torsion, eccentrical bending, and also subjected to buckling, eccentrical compressive and eccentrical tensile stresses: in all these cases the pertaining parameters of Weibull's function are determined. Thirdly, sundry engineering applications of said discipline are set out in such fields as, for example, soil mechanics, rock mechanics, seismology, nuclear reactors industry, fatigue, and concrete pavements. At last a brief description of research work now in progress is given.